LITERATURE REVIEW: CHEMICAL CONTENT AND PHARMACOLOGICAL ACTIVITY OF KERSEN LEAF (Muntingia calabura L.) - Asman Sadino; Sri Adi Sumiwi; Sari Sumarni (Universitas Muhammadiyah Magelang, 2022)
Kersen (Muntingia calabura L.) is known as a plant that is often used as a tree to absorb air pollution and shade on the roadside. Low economic value and public knowledge about the benefits of cherry as a medicinal and food ingredient is still minimal. The part that can be used as a medicinal ingredient comes from cherry leaves. The purpose of this review article is to provide information related to the chemical content and pharmacological activity of cherry leaves that can treat various diseases. The method used in making this article review is a literature study. The literature sources in this article review were obtained from national journals and international journals published in the last 10 years (2010-2020), which were carried out online through the search engines Google Scholar, Pubmed, and NCBI, using the keywords